Systematic effects and mitigation strategies in observations of cosmic re-ionisation with the Hydrogen Epoch of Reionization Array - Charles, Ntsikelelo (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2024)
The 21 cm transition from neutral Hydrogen promises to be the best observational probe of the Epoch of Reionisation (EoR). It has driven the construction of the new generation of lowfrequency radio interferometric arrays, including the Hydrogen Epoch of Reionization Array (HERA). The main difficulty in measuring the 21 cm signal is the presence of bright foregrounds that require very accurate interferometric calibration. However, the non-smooth instrumental response of the antenna as a result of mutual coupling complicates the calibration process by introducing non-smooth calibration errors. Additionally, incomplete sky models are typically used in calibration due to the limited depth and resolution of current source catalogues. Combined with the instrumental response, the use of incomplete sky models during calibration can result in non-smooth calibration errors. These, overall, impart spectral structure on smooth foregrounds, leading to foreground power leakage into the EoR window. In this thesis we explored the use of fringe rate filters (Parsons et al., 2016) as a mean to mitigate calibration errors resulting from the effects of mutual coupling and the use of an incomplete sky model during calibration. We found that the use of a simple notch filter mitigates calibration errors reducing the foreground power leakage into the EoR window by a factor of ∼ 102. Thyagarajan et al. (2018) proposed the use of closure phase quantities as a means to detect the 21 cm signal, which has the advantage of being independent (to first order) from calibration errors and, therefore, bypasses the need for accurate calibration. In this thesis, we explore the impact of primary beam patterns affected by mutual coupling on the closure phase. We found that primary beams affected by mutual coupling lead to a leakage of foreground power into the EoR window, which can be up to ∼ 104 times and is mainly caused by the unsmooth spectral structure primary of primary beam sidelobes affected by mutual coupling. This power leakage was confined to k < 0.3 pseudo h Mpc−1. Lastly, we also proposed and demonstrated an analysis technique that can be used to derive a flux scale correction in post-calibrated HERA data. We found that after applying flux scale correction to calibrated HERA data, the bandpass error reduces significantly, with an improvement of 6%. The derived flux scale correction was antenna-independent, and it can be applied to fix the overall visibility spectrum scale of H4C data post-calibration in a fashion similar to Jacobs et al. (2013).
Keywords: Cosmology; Astrophysics; Radio astronomy; Hydrogen Epoch of Reionization Array; Epoch of reionization